A cross-sectional study on the correlation between cytokines in a pelvic environment and tubal factor infertility - Jiacong Yan; Chengbo Liu; Han Zhao; Chunyan Wang; Huimei Yao; Qiong Lu; Jia Liu; Yun Feng (BMC, 2020)
Abstract Background This cross-sectional study aimed to evaluate the levels of tumor necrosis factor-alpha (TNF-ɑ), interleukin-8 (IL-8), interleukin-6 (IL-6), and transforming growth factor-beta 1 (TGF-β1) in patients with primary and secondary tubal factor infertility (TFI) compared with fertile subjects, and to compare immune indexes in the serum and peritoneal fluid samples obtained from patients with TFI. Methods The pelvic fluid and peripheral blood of patients with TFI diagnosed by hysteroscopy and laparoscopy were taken as the study objects. The pelvic fluid and peripheral blood of patients who underwent hysteromyomectomy at the same time were taken as the control group. The contents of TNF-ɑ, IL-8, IL-6, and TGF-β1 in serum and peritoneal fluid were determined by enzyme-linked immunosorbent assay, and the levels of these cytokines in serum and pelvic fluid were compared between the two groups. Results Patients with secondary TFI showed significantly higher levels of TNF-ɑ, IL-8, IL-6 and TGF-β1 in the serum (26.15 ± 3.51 vs. 19.61 ± 0.157, 32.18 ± 15.13 vs. 5.73 ± 1.99, 38.84 ± 3.46 vs. 30.48 ± 0.61, and 38.37 ± 3.14 vs. 32.25 ± 1.69, respectively) and peritoneal fluid samples (129.73 ± 183.4 vs. 34.63 ± 0.56, 111.44 ± 207.42 vs. 15.34 ± 0.41, 80.01 ± 109.91 vs. 15.67 ± 0.52, and 82.54 ± 115.99 vs. 45.34 ± 0.41, respectively) compared with the control group. Patients with primary TFI exhibited significantly elevated concentration of TNF-α, IL-8, IL-6 and TGF-β1 in the peritoneal fluid samples (36.88 ± 2.67 vs. 34.63 ± 0.56, 19.47 ± 3.51 vs. 15.34 ± 0.41, 80.01 ± 109.91 vs. 15.67 ± 0.52, and 82.54 ± 115.99 vs. 45.34 ± 0.41, respectively) when compared to the controls. In patients with secondary infertility, the levels of TNF-α (26.15 ± 3.51 vs. 129.73 ± 183.4), IL-8 (32.18 ± 15.13 vs. 111.44 ± 207.42), IL-6 (38.84 ± 3.46 vs. 80.01 ± 109.91) and TGF-β1 (38.37 ± 3.14 vs. 82.54 ± 115.99) in the serum were significantly lower than those in the peritoneal fluid, whereas no significant difference was observed in the primary TFI group between the serum and peritoneal fluid cytokines levels. Conclusion The expression of cytokines in the pelvic environment of patients with TFI is upregulated compared to patients who do not have infertility issues. The detection of cytokines TNF-ɑ, IL-6, IL-8, and TGF-β1 in the pelvic fluid of tubal infertility patients can allow for further understanding of the etiology of TFI.